Recent Progress in Wastewater Treatment: Exploring the Roles of Zero-Valent Iron and Titanium Dioxide Nanoparticles - Amin, Hamza; Tayyab, Attia; Umair, Muhammad; Naveed, Muhammad Rashid; Yaseen, Hafiza Rabia; Qasim, Muhammad; Muzammal, Muhammad; Saif, Sumaira; Ali, Muhammad Awais; Sultan, Muhammad Abid (Indus Journal of Bioscience Research, 2025)
Significant environmental issues have been created by the growing outflow of urban and industrial wastewater, which calls for the development of sophisticated and effective treatment systems. Zero-valent iron (ZVI) and titanium dioxide (TiO₂) nanoparticles have become well-known among developing solutions because of their exceptional reactivity, affordability, and potential for large-scale applications. With an emphasis on their processes, efficacy, and difficulties, this paper examines the most recent developments in the application of ZVI and TiO₂ nanoparticles for wastewater treatment. TiO₂ nanoparticles have remarkable photocatalytic qualities, efficiently breaking down persistent organic pollutants under UV and visible light, whereas ZVI nanoparticles have high reductive capabilities, allowing the removal of heavy metals, chlorinated compounds, and organic pollutants. Their efficiency, stability, and reusability have been improved by recent alterations such as doping, surface functionalization, and hybrid nanocomposites. However, obstacles to wider use include recovery issues, possible ecotoxicity, and nanoparticle aggregation. To increase the sustainability and viability of ZVI and TiO₂ applications, this study also covers cutting-edge techniques, including magnetic separation, green synthesis, and integration with other treatment methods. Future studies should concentrate on creating scalable treatment plans, assessing long-term environmental effects, and improving nanoparticle design. ZVI and TiO₂ nanoparticles have enormous potential to transform wastewater treatment and support global water sustainability by solving these issues.